Alpine tourism - Andrea Macchiavelli (Revue de Géographie Alpine)
The spectacular increase in tourism in the Alps in recent decades has been founded mainly on the boom in skiing, resulting in both strong real estate development and an increasing array of infrastructures and ski runs. Today the ski market seems to have virtually reached saturation point and the winter sports sector needs to diversify its offer through innovation. After a review of the main factors of change in mountain tourism, the paper presents a grid for interpreting the life cycle of alpine destinations, identifying the phases that characterize their evolution. The conditions that may favour innovation in alpine tourism are then identified, as well as the contradictions that frequently accompany them. In most cases, innovation is the result of a process that begins within the alpine community, frequently encouraged and supported by national and international institutions and with whose help structural difficulties are successfully overcome.